Which expression represents the composition [g o f o h](x) for the functions below?
f(x) = 5x – 4
g(x) = 5x3
h(x) = 3x

5(15x – 4)^3
(75x – 20)^3
5(5x – 4)^3
675x^3 – 4

Respuesta :

Answer:

[tex]5(15x-4)^3[/tex]

Step-by-step explanation:

[tex]f(x) = 5x - 4[/tex]

[tex]g(x) = 5x^3[/tex]

[tex]h(x) = 3x[/tex]

[tex](gofoh)(x)=g(f(h(x)))[/tex]

Replace h(x) first

[tex]g(f(h(x)))=g(f(3x))[/tex]

Now we plug in 3x in f(x)

[tex]g(f(h(x)))=g(f(3x))=g(5(3x)-4)=g(15x-4)[/tex]

Now we plug in 15x-4 in g(x)

[tex]g(f(h(x)))=g(f(3x))=g(5(3x)-4)=g(15x-4)=5(15x-4)^3[/tex]

Answer:

A. 5(15x – 4)3

Step-by-step explanation:

ACCESS MORE